Sex Hormones and rheumatoid factor : a possible link between reproductive hormones patterns and the onset of rheumatoid arthritis among women in Khartoum, Sudan (2016)
Background: Sex hormones are believed to contribute to the risk of rheumatoid arthritis (RA) because of the disease's female preponderance, especially during the child-bearing years, and because of the dramatic improvements seen during pregnancy. Objective: To investigate the association between reproductive hormones, follicle stimulating hormone (FSH), luteinizing hormone (LH) and prolactin (PRL) patterns and the risk of developing rheumatoid arthritis disease among females in Khartoum, Sudan. Participants and methods: The study involved a total of 76 healthy females during their fertile years and age between 18-45years. Reproductive hormones (FSH, LH and PRL) were obtained using the enzyme-immunoassay method by Cobas e411or Tosho Biosciences AIA 360 full automated analyzers. Then RF levels were examined using latex card qualitative method and those which were confirmed positive were further estimated using semi-quantitative method. Results: 11 (14.86%) females participants showed positive RF results. The risk of RA appeared to be increased among women with elevated reproductive hormones levels. In which the positive RF women showed mostly increased hormonal levels when compared to RF negative women. 12 females participants who have had an increased reproductive hormones levels have completed a life style related questionnaire and the data revealed that most of them were living unhealthy life style including unhealthy food, lack of exercise and high caffeine consumption. Conclusion: Further researches are required to explore the biological mechanisms behind these findings, but our results contribute to the knowledge of hormonal/reproductive factors, and their impact on the RA development.